Peranan Roh Kudus Dalam Hidup Gereja - Angelo Luciani Moa Dosi Woda (Pusat Riset dan Inovasi Nasional, 2024)
In this paper, we try to reflect on one of the important aspects of the Church's faith, namely the essential belief in the Trinity: Father, Son, and Holy Spirit. In particular, we will reflect on the universal Church's faith in the Holy Spirit. Although this article is very limited, we would like to make an important contribution to the relationship between the Holy Spirit in the life of the Trinity and the life of the Church. Therefore, the author tries to analyze the works of Joseph Cardinal Ratzinger (Pope Benedict XVI) on the relationship of the Holy Spirit as the Spirit of the Communion of the Father and the Son and the relationship of the Holy Spirit with the Church. In other words, we will find an unbroken continuity, an inseparable, organic dynamic between the Holy Spirit as the Spirit of the Trinity and the role of the Holy Spirit as the Principle of Communion in the Church.